Verifikasi dan Validasi Data Keluarga Miskin melalui Aplikasi Bangkit di Kecamatan Sukahaji Kabupaten Majalengka Provinsi Jawa Barat - Rahma, Elza Amira; Nurrahman, Agung (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Tjut Nyak Dhien, 2025)
The purpose of this service is to validate and verify poverty data through the Bangkit application which is implemented in Sukahaji District. The service method used is data verification and validation. The results of the service activities show that the inclusion of photos of external and internal house conditions and information that classifies a population as poor or not, obtaining data through work practices, interviews, documentation and recording population data through the application is very important in classifying the poor. Various features in the Bangkit app have been improved. At least, in the last three weeks there have been five improvements that greatly facilitate the data collection of the poor. There was a decrease in the poverty rate, which initially amounted to 1,647 families, reduced to 1,556 families. In conclusion, the data verification and validation activities conducted by the Team can encourage the updating of data on poor families.